Rectal Ischemia Mimicked Tumor Mass - Nicolaos Zikos; Panagiota Aggeli; Evangelia Louka; George Pappas-Gogos (Case Reports in Gastrointestinal Medicine)
Ischemic proctitis is a rare disease which is usually encountered in elderly with comorbidities. We present a case of an 80-year old man with severe coronary disease who presented with severe hematochezia and hypotension. Endoscopy revealed a rectal mass 3-4 cm above the dental line and rectosigmoid mucosal inflammation compatible with ischemic colitis. The rectal insult was so intense that it resembled a neoplasmatic lesion. We discuss the causes, the prognostic factors, and the clinical and therapeutic challenges of this rare, albeit life-threatening entity, and we review the relative literature. A percentage of 10%–20% of patients with ischemic colitis usually have a distal potentially obstructing lesion or disorder such as cancer, diverticulitis or fecal impaction. Ischemic colitis, when mucosal and submucosal edema is severe and hemorrhagic nodules are large enough, can mimic a neoplasmatic lesion. The best treatment approach is a conservative management initially with a close clinical followup and after stabilization a repetition of rectal endoscopy with new biopsies. Early recognition of this clinical entity is of paramount importance to implement appropriate therapy (conservative or surgical) and avoid potentially fatal treatment of presumed inflammatory or infectious bowel diseases.